Branding Analysis of Culinary Business in the Digital Era from the Perspective of Sharia Economic Law - Murti Eliza; Eficandra; Elsy Renie; Suprio Jaya Putra (Majapahit Journal of Islamic Finance and Management, 2026)
The digital transformation has fundamentally changed the landscape of culinary business branding. However, the evolving practices often overlook Islamic ethical principles, such as dishonesty in promotions, review manipulation, and psychological exploitation of consumers. This research aims to analyze culinary business branding in the digital era from the perspective of Sharia Economic Law. The research method used is a literature review with a qualitative approach, drawing from books, international and national scientific journal articles, as well as research reports published between 2020 and 2025. The research findings show that digital branding has transformed into a collaborative process between brands and consumers through various digital platforms, where reputations are built participatively. Sharia Economic Law principles such as justice, honesty, transparency, and prohibitions on gharar, maysir, riba, and tadlis should form the ethical foundation for all digital branding practices. Analysis of endorsement strategies, reviews, social media advertising, flash sales, and viral marketing reveals that many practices potentially involve elements of dishonesty and lack of transparency prohibited by Sharia. The implementation of Sharia branding faces multidimensional challenges, including limited understanding among business practitioners, technological disparities, high compliance costs, and competitive pressures. This research concludes that Sharia branding is a holistic commitment to integrating spiritual values into brand management to realize benefits and blessings. Implementation of the research findings includes credible halal certification, the application of honesty and transparency in digital marketing, responsible management of consumer interactions, and collaboration with stakeholders to build a culinary digital branding ecosystem compliant with Sharia principles.